Biochemical mechanism of modulation of human P-glycoprotein (ABCB1) by curcumin I, II, and III purified from Turmeric powder - Chearwae W. (2014)
P-glycoprotein (Pgp, ABCB1) is an ATP-dependent drug efflux pump linked to development of multidrug resistance (MDR) in cancer cells. Previously [Biochem Pharmacol 2002;64:573-82], we reported that a curcumin mixture could modulate both function and expression of Pgp. This study focuses on the effect of three major curcuminoids--curcumin I, II and III purified from a curcumin mixture--on modulation of Pgp function in a multidrug resistant human cervical carcinoma cell line (KB-V1). The similar IC(50) values for cytotoxicity of curcuminoids of KB-V1, and KB-3-1 (parental drug sensitive cell line) suggest that these curcuminoids may not be substrates for Pgp. Treating the cells with non-toxic doses of curcuminoids increased their sensitivity to vinblastine only in the Pgp expressing drug resistant cell line, KB-V1, and curcumin I retained the drug in KB-V1 cells more effectively than curcumin II and III, respectively. Effects of each curcuminoid on rhodamine123, calcein-AM, and bodipy-FL-vinblastine accumulation confirmed these findings. Curcumin I, II and III increased the accumulation of fluorescent substrates in a dose-dependent manner, and at 15 microM, curcumin I was the most effective. The inhibitory effect in a concentration-dependent manner of curcuminoids on verapamil-stimulated ATPase activity and photoaffinity labeling of Pgp with the [(125)I]-iodoarylazidoprazosin offered additional support; curcumin I was the most potent modulator. Taken together, these results indicate that curcumin I is the most effective MDR modulator among curcuminoids, and may be used in combination with conventional chemotherapeutic drugs to reverse MDR in cancer cells.